Smoking-Related Interstitial Fibrosis: Evidence of Radiologic Regression with Advancing Age and Smoking Cessation. (2nd November 2017) - Fabre, Aurélie; Treacy, Ann; Lavelle, Lisa P; Narski, Maciek; Faheem, Nazia; Healy, David; Dodd, Jonathan D.; Keane, Michael P.; Egan, James J.; Jebrak, Gilles; Mal, Hervé; Butler, Marcus W.
ABSTRACT: More data are needed regarding the radiology, co-morbidities and natural history of smoking-related interstitial fibrosis (SRIF), a common pathological finding, mainly described heretofore in association with lung cancer, where respiratory bronchiolitis (RB) usually co-exists. We prospectively acquired high resolution CT scan data (edge-enhancing lung reconstructions) to detect any radiologic interstitial lung abnormality (ILA) in individuals who ultimately underwent surgical lobectomy for lung cancer ( n = 20), for radiologic/pathologic correlation. We also re-examined other smoking-related benign histologic cases: chronic obstructive pulmonary disease (COPD lung explants, n = 20), alpha 1-antitrypsin deficiency (A1AT, explanted lungs n = 20), combined pulmonary fibrosis and emphysema (CPFE, n = 8) and idiopathic pulmonary fibrosis (IPF, n = 10). Finally, we pooled our data with all peer-reviewed published data describing histologic SRIF of known ILA status. SRIF was observed in 40% of cancer lobectomies, mean (±SD) age 65.8 ± 8.7 years, none of whom had ILA. SRIF was observed in other smoking-related benign diseases (COPD 35%, A1AT 20%, CPFE 25%, and IPF 10%). 71.4% of benign SRIF cases had no RB (nearly all ex-smokers) versus 0% of cancer-associated SRIF cases ( P = 1.7 × 10 −3 ). Pooled data showed that those SRIF subjects without ILA were 15.05 years older than those with ILA (95% confidence interval 8.99 to 21.11, P = 2.5 × 10 −5 ) and more likely to be former smokers ( P = 7.2 × 10 −3 ). SRIF is frequently found without lung cancer, and mostly without RB in former smokers. SRIF is less likely to have ILA in older subjects and with smoking cessation, which could represent RB+/−SRIF regression.